Le récit mythique d’une conversion : La Argentina à l’Athénée de Madrid - Hélène Frison (Cahiers de Civilisation Espagnole Contemporaine)
In an interview she gave to the French press in 1935, Antonia Mercé, a.k.a. La Argentina, dates her success in Spain to April 16, 1915. That evening, while she performed at the Athenaeum in Madrid in front of "intellectuals, painters, writers, poets, musicians," a double shift took place: while the spectators experienced a kind of epiphany of the dance, she became aware of what her priesthood would be from then on - to embody "the spirit of the Spanish dance". First, the study of the Spanish press published at the end of that particular evening will allow us to highlight the discrepancies, distortions and amalgams that appear in the retrospective narrative of the artist. Then we will try to present the motivations which may have presided over the construction of this story with the appearance of a conversion.